(untitled) (Res Medica, 2013)
Twenty years ago, it was generally considered that breast cancer was readily accessible to radical surgery and that radical surgery had more to offer here than perhaps anywhere else in the body. In the intervening years, this pseudo-complacency has suffered a series of rude shocks, until to-day the pendulum has swung full distance and radical mastectomy plays but a minor role in the treatment of carcinoma of the breast. The now obvious gaps in our armamentarium have been filled by X-ray therapy, with or without local surgery, by the use of the sex endocrines and the cortico-steroids and by what may be termed “ physiological” operations on various endocrine glands.